DETERMINANTS OF FINANCIAL MANAGEMENT BEHAVIOR OF SEMARANG CITY SMEs - C Tri Widiastuti; Nuria Universari; Irene Nathalia Setiawan (Jurnal Akuntansi Dan Bisnis Indonesia (JABISI), 2023)
Financial management behavior is one of the important things in the domain of financial science. Great financial management behavior can help SMEs’ stakeholders to be responsible for the financial management of money and assets in ways that are seen as productive. Financial literacy, financial attitudes, and intentions as intervening variables are factors that can influence SMEs’ financial management behavior. The purpose of this research is to determine the effect of financial literacy, financial attitudes, and intentions as intervening variables on SMEs’ financial management behavior. The method applied in this research is quantitative with a questionnaire used as a medium for data collection. A proportionate stratified random sampling technique with Proportionate Stratified Random Sampling was used as the sampling strategy in this study. Primary data were analyzed using the Statistical Package for Social Science (SPSS) technique with multiple regression analysis methods and the Sobel test. The results show that in Model I there is a positive and significant effect between financial literacy and financial attitudes toward behavioral intentions. On the other hand, there is a positive and significant effect between financial literacy, financial attitudes, and intention on financial management behavior. Intentions can convey the impact of financial literacy and financial attitudes toward financial management behavior.